Molecular identification of dengue virus binding protein on filopodia of vero cells - Aliyu, Isah Abubakar (2017)
Despite much efforts to control dengue virus, there is still neither scientifically proven effective drug nor an effective internationally licensed vaccine to treat or control dengue. Recent evidence has demonstrated that dengue virus requires an active filopodia formation for successful infection. However, the precise mechanism for dengue virus interaction with filopodia to enhance virus infection is not fully understood. Therefore, the present study was designed to identify the dengue virus 2 binding protein that could be responsible for enhanced virus infection upon filopodia formation. Filopodia formation in Vero cells was induced with bradykinin and a combination of virus overlay protein binding assay (VOPBA) and LC-MS/MS was employed to identify annexin II as a dengue virus 2 binding protein on filopodia-induced cells. Translocation of annexin II to the external leaflet of plasma membrane following filopodia formation was demonstrated by immunocytochemistry staining and western blotting analysis. Down-regulation of plasma membrane annexin II was observed in response to dengue virus 2 infection. Moreover, anti-annexin II antibody inhibited virus binding in an antibody-dependent binding inhibition assay and a dose-dependent reduction in both dengue virus infection level and virus production was demonstrated in an antibody-mediated infection inhibition assay. Similarly, siRNA-mediated knockdown of annexin II gene significantly reduced virus infection level as well as virus production. Confocal microscopic examination showed extracellular and intracellular colocalization between annexin II and dengue virus 2 E glycoprotein, and co-immunoprecipitation assay confirmed that annexin II interacted with dengue virus 2 E glycoprotein. Furthermore, the putative annexin II interaction site on dengue virus 2 E glycoprotein was predicted using molecular docking and the interaction was likely to occur at residues Ile-380 to Leu-389 of E glycoprotein, with Ser-22 to Asn-32, Leu-300 to Tyr-317 and Lys-328 to Asp-338 of annexin II. Data from the present study reported for the first time the expression of a dengue virus 2 binding protein upon filopodia formation, which might be involved in dengue virus 2 binding, internalization and intracellular trafficking. Thus, the results could explain the likely reason behind enhanced virus infection observed upon filopodia formation and could be a potential target for the development of a novel antiviral.